"Laser Discoverers" – Web‐based User‐generated Content in Heritage Detection in Poland. Issue 2 (4th May 2016) - Stereńczak, Krzysztof; Zapłata, Rafal; Sztampke, Maciej; Bałazy, Radomir
Abstract: This article presents the results and potential of using volunteered geographic information (VGI) in heritage detection. Research was completed under the project entitled "Laser Discoverers – non‐invasive examination and documentation of archeological and historical objects in the Świętokrzyskie Voivodeship", carried out as a part of the Ministry of Science and Higher Education program entitled "The Paths of Copernicus". Within the project, strong emphasis was placed on promotional and awareness‐raising activities, to involve as many voluntary users as possible. Project participants had at their disposal a web application, which provided access to a digital terrain model (DTM) where they identified possible heritage objects. All samples of data were additionally available in eight variants of sunshine, based on the simulation of sunlight from eight directions and at a constant angle. In total, 5, 989 elementary areas with dimensions of 100 × 100 m were used for the project. After conducting a field inventory, Internet users together with specialists were able to recognize several thousands of potential archaeological and historic objects. During the project, approximately 10% of those features were verified through non‐invasive (field survey) work, with 75% success.